Eficiência do uso de fósforo em genótipos de feijão caupi - Almeida, Idaiane Costa Fonseca (2016)
Cowpea (Vigna unguiculata (L.) Walp.) Also known as cowpea, Vigna beans, string bean is an edible legume with good ability to fix nitrogen and undemanding in soil fertility. The cowpea genotypes respond differently to match nutrient availability in accordance with this soil. This study aimed to evaluate the phosphorus use efficiency in cowpea genotypes. The experiment was conducted at the Experimental Farm Rafael Fernandes, 20 km away from the seat of the municipality of Mossoro in soil classified as Ultisol from April to July 2015. The experimental design was a randomized complete block in a factorial 2 x 5 with four replications. The treatments were a combination of two phosphorus levels (0 and 60 kg ha-1 of P2O5) and five genotypes of cowpea (Paulistinha, BRS Xiquexique Gold Raindrop, Corujinha and Cow Rib). Each plot consisted of four rows of plants, measuring 3.0 m in length, spaced 1.0 x 0.3 m with two plants per hole .. The genotypes responded significantly to the increase in the level of phosphorus in soil with increases in the number of seeds per pod, number of pods per plant, yield, dry matter and accumulation of P plant. As for the use of phosphorus, the BRS Xiquexique genotype was considered efficient and responsive, and Costa Paulistinha efficient cow and nonresponsive, Corujinha was classified as inefficient and responsive and Pingo Gold as inefficient and unresponsive